(untitled) (ALAM AL-KUTUB, 2026)
The article presents an analytical review of a doctoral thesis by researcher Mina Ashraf Makar, titled "The Role of Artificial Intelligence in Book Marketing: A Comparative Study of Arab and Foreign Publishers", supervised by Prof. Raouf Abdel Hafeez Al-Hilal, with the participation of Prof. Amjad Abdel Hadi Al-Gohary, Department of Information Studies, Faculty of Arts, Ain Shams University, 2026. The study investigates the integration of AI applications and tools in the development of book marketing strategies, utilizing a comparative descriptive methodology on a sample of Arab and international publishing houses to evaluate the levels of publishers’ awareness regarding AI technologies, patterns and modes of practical implementation, and their impact on the marketing mix elements and sales growth. The study found that AI is identified as a fundamental strategic pillar for modern book marketing, with a clear superiority of foreign publishers in terms of awareness and application compared to Arab publishers, whose level of awareness and use was found to be moderate. The study also highlighted the most effective strategies, such as contextual marketing, enormous data analytics, and predictive marketing, emphasizing that adopting these tools contributes to enhancing the competitiveness of publishing houses. The study concluded by presenting a proposed vision for implementing AI within the Arab publishing environment, supported by practical recommendations, most notably supporting smart transformation in the publishing industry, building human capacities, and strengthening research and technological partnerships.